2007
DOI: 10.1007/s11274-007-9525-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species induction of antibacterial activity produced by epibiotic bacteria isolated from Indian marine sponge Pseudoceratina purpurea

Abstract: Four antibiotic producing bacteria were isolated from the surface of the marine sponge Pseudoceratina purpurea and exposed to living cells of two human pathogenic bacteria as well as some marine fouling bacteria to induce the production of antimicrobial activity. Experimental results showed that these four marine epibiotic bacteria enhanced their antibacterial production, when exposed to these test strains. The highest induction was exhibited by the sponge isolate PS79 against fouling bacterium FB-9 (from 3 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Of the 210 bacterial isolates from the brown alga Laminaria saccharina, 103 inhibited the growth of at least 1 of the pathogens tested (Wiese et al 2009). By contrast, out of 92 isolates from Japanese red algae, only ca one-third of the isolates inhibited the growth of environmental and pathogenic bacteria (Kanagasabhapathy & Nagata 2008). Similarly, a low percentage ($12%) of microbes with antibacterial properties belonging to the α-and γ-proteobacteria were isolated from the green alga Ulva australis and the red alga Delisea pulchra, respectively (Penesyan et al 2009).…”
Section: Antibacterial Activity Heterotrophic Bacteriamentioning
confidence: 98%
“…Of the 210 bacterial isolates from the brown alga Laminaria saccharina, 103 inhibited the growth of at least 1 of the pathogens tested (Wiese et al 2009). By contrast, out of 92 isolates from Japanese red algae, only ca one-third of the isolates inhibited the growth of environmental and pathogenic bacteria (Kanagasabhapathy & Nagata 2008). Similarly, a low percentage ($12%) of microbes with antibacterial properties belonging to the α-and γ-proteobacteria were isolated from the green alga Ulva australis and the red alga Delisea pulchra, respectively (Penesyan et al 2009).…”
Section: Antibacterial Activity Heterotrophic Bacteriamentioning
confidence: 98%
“…It has been previously reported that individual bacterial strains isolated from epibiotic marine biofilms are capable of inhibiting the growth of S. aureus (Burgess et al 1999;Kanagasabhapathy and Nagata 2008). It has also been shown that individual marine biofilm isolates can be induced to express increased activity against S. aureus when grown in the presence of spent culture media from S. aureus, or in co-culture with S. aureus (Burgess et al 1999;Kanagasabhapathy and Nagata 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that individual marine biofilm isolates can be induced to express increased activity against S. aureus when grown in the presence of spent culture media from S. aureus, or in co-culture with S. aureus (Burgess et al 1999;Kanagasabhapathy and Nagata 2008). Similarly, Bacillus subtillus has been reported to have inducible activity against S. aureus (Tabbene et al 2011), and marine epibiotic isolates to have inducible activity against Pseudomonas aeruginosa (Dusane et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Many silent biosynthetic genes are only activated under specific conditions for the enhance production of antibiotics (Scherlach and Hertweck, 2009). Thus, new cultivation approach, particularly strategies similar to the natural habitats in which microorganisms defending themselves against competitive bacteria can be used to enhance the production of secondary metabolites (Kanagasabhapathy and Nagata, 2007). So, co-culture of microorganisms can be used as an alternative way to screen production antimicrobial drugs.…”
Section: Introductionmentioning
confidence: 99%